PENGARUH BUDAYA FLEXING DIGITAL TERHADAPPRESTASI BELAJAR MATA PELAJARAN AKIDAH AKHLAKKELAS IX MADRASAH TSANAWIYAH NEGERI 8 BOYOLALITAHUN AJARAN 2025/2026 - Shofika Ahadia; Edy Muslimin (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effect of digital flexing culture on students’ learning achievement in the Aqidah Akhlak subject at MTs Negeri 8 Boyolali in the 2025/2026 academic year. This research employed a quantitative approach using simple linear regression analysis. The sample consisted of 33 students selected through purposive sampling from a population of 128 students. Data were collected through Likert-scale questionnaires to measure digital flexing culture and documentation of students’ academic scores. Data were analyzed using descriptive statistics, normality test (Shapiro–Wilk), linearity test (ANOVA), and hypothesis testing with SPSS 25. The findings indicate that the level of digital flexing culture is relatively high (mean = 27.3), while students’ learning achievement is also categorized as high (mean = 80.87). However, regression analysis shows that digital flexing culture does not have a significant effect on learning achievement (t = 0.710 < 1.695; Sig. = 0.483 > 0.05), although it has a very weak positive direction (β = 0.095). This study provides empirical evidence that specific digital cultural phenomena, such as flexing behavior, do not directly influence academic achievement in Islamic value-based education, highlighting the stronger role of internal factors such as self-control and moral values.